Energy Consumption, Maritime Trade and Economic Growth Nexus: Evidence from Nigeria - Aruwei, Porwekobowei; Etugbo, Christopher Oghenemaro; Agboniyokpa, Ikhisemon-Oje (Journal of Environmental and Energy Economics, 2025)
Although Nigeria’s maritime trade and energy demand is on the rise, the empirical nature of the relationship between energy consumption, maritime trade and economic growth is yet to be determined. Current literature is predominantly based on developed economies or considers these variables separately and ignores the structural and energy peculiarities of Nigeria. This loophole restricts evidence-based policy making to sustainable maritime and economic growth. Hence, an in-depth empirical study is needed to comprehend the dynamics of the effect of energy consumption together with maritime trade on the economic growth in Nigeria. This study therefore explored the nexus between maritime trade, energy consumption and economic growth in Nigeria. Time series data between the year 1990 and 2023 was used in the study. Analysis of the relationships between the variables in the study was done using the Vector Autoregression (VAR) technique. The study findings indicated that the VAR model predicts the most significant determinant of each variable as its one period lag value. The Impact Response Function and forecast error variance decomposition revealed that the energy consumption of fossil source, electricity power consumption, and maritime trade has a positive impact on economic growth in the long run and short run. The study concluded that energy consumption and maritime trade are crucial for economic growth. The study therefore recommended that government should invest more in the energy infrastructure, production of hydro energy especially small and medium hydro power plants, government also needs to enhance the capacity and competitiveness of the maritime trade by modernizing the seaports.